Recentes tentativas de consolidação da Ciência da Informação enquanto campo científico no contexto das reflexões sobre a ciência - Andre Felipe Pinto Duarte (2001)
This research presented some preliminary reflections on recent debates on the nature and identity of Information Science as a research field that intends to be considered scientific. Attempts were made to identify possible dialogues among debates about metatheoretical aspects of Information Science and some of the recent paradigms suggested by various authors (Edgar Morin, Alan Chalmers, Boaventura de Sousa Santos etc...) In order to do so, it was necessary to carry out an analysis on some of the main events in the history of science and to identify the principles suggested by recent paradigms. Those principles were presented as alternatives for obstacles and inadequacies of the dominant paradigm of modern scientific rationality towards information science.